Navigating the nano-bio immune interface: advancements and challenges in CNS nanotherapeutics - Moulton, Chantalle; Baroni, Anna; Quagliarini, Erica; Leone, Lucia; Digiacomo, Luca; Morotti, Marta; Caracciolo, Giulio; Podda, Maria Vittoria; Tasciotti, Ennio (Frontiers in Immunology, 2024)
In recent years, significant advancements have been made in utilizing nanoparticles (NPs) to modulate immune responses within the central nervous system (CNS), offering new opportunities for nanotherapeutic interventions in neurological disorders. NPs can serve as carriers for immunomodulatory agents or platforms for delivering nucleic acid-based therapeutics to regulate gene expression and modulate immune responses. Several studies have demonstrated the efficacy of NP-mediated immune modulation in preclinical models of neurological diseases, including multiple sclerosis, stroke, Alzheimer’s disease, and Parkinson’s disease. While challenges remain, advancements in NPs engineering and design have led to the development of NPs using diverse strategies to overcome these challenges. The nano-bio interface with the immune system is key in the conceptualization of NPs to efficiently act as nanotherapeutics in the CNS. The biomolecular corona plays a pivotal role in dictating NPs behavior and immune recognition within the CNS, giving researchers the opportunity to optimize NPs design and surface modifications to minimize immunogenicity and enhance biocompatibility. Here, we review how NPs interact with the CNS immune system, focusing on immunosurveillance of NPs, NP-induced immune reprogramming and the impact of the biomolecular corona on NPs behavior in CNS immune responses. The integration of NPs into CNS nanotherapeutics offers promising opportunities for addressing the complex challenges of acute and chronic neurological conditions and pathologies, also in the context of preventive and rehabilitative medicine. By harnessing the nano-bio immune interface and understanding the significance of the biomolecular corona, researchers can develop targeted, safe, and effective nanotherapeutic interventions for a wide range of CNS disorders to improve treatment and rehabilitation. These advancements have the potential to revolutionize the treatment landscape of neurological diseases, offering promising solutions for improved patient care and quality of life in the future.